Adipose derived stem cells for the peripheral nerve regeneration: review of techniques and clinical implications - Fizzah Arif; Mohammad Fazlur Rahman; Ceemal Fareed Khan (Journal of the Pakistan Medical Association, 2023)
Adipose tissue is considered as a multipotent organ with multiple cellular varieties, like adipose derived stem cells with ability to differentiate into nerve cells. This review is an attempt to summarize the techniques of harvesting, isolating and delivery of adipose derived stem cells to injured nerve area and various interactions involved in the release of neurotrophic and angiogenic factors from stem cells. Neuro-regenerative potential of ADSCs is explained on the basis of “Paracrine hypothesis”, according to which ADSCs secrete multiple neurotrophic factors and upregulates secretion of these neurotrophic factors by Schwann cells, leading to improved myelination, regeneration and decreases nerve fibrosis. ADSCs are easily available in abundance and undergo multi-step processing before grafting to nerve injury site. Acute inflammation, hypoxia and co-culturing with Schwann cells promotes neural differentiation of ADSCs. ADSCs and Schwann cells are reported to have similar mitogenic and differentiation factors, Continued...